Integral Methods in Science and Engineering 2019
DOI: 10.1007/978-3-030-16077-7_2
|View full text |Cite
|
Sign up to set email alerts
|

On the Flow of a Viscoplastic Fluid in a Thin Periodic Domain

Abstract: We study in this paper the steady incompressible nonlinear flow of a Bingham fluid in a thin periodic domain, which is a model of porous media. The model of thin porous media of thickness much smaller than the parameter of periodicity was introduced in [Zh08], where a stationary incompressible Navier-Stokes flow was studied. Recently, the model of the thin porous medium under consideration in this paper was introduced in [FaEtAl16], where the flow of an incompressible viscous fluid described by the stationary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In the recent paper [5], the authors present a model of Bingham flow in a thin periodic domain which contains an array of obstacles modelized as vertical cylinders. Up to our knowledge, the first convergence result on Bingham flow in thin periodic domains is due to [1], followed by [2]. We refer to [18] for Bingham flows in periodic domains of infinite length.…”
Section: (): V-volmentioning
confidence: 98%
“…In the recent paper [5], the authors present a model of Bingham flow in a thin periodic domain which contains an array of obstacles modelized as vertical cylinders. Up to our knowledge, the first convergence result on Bingham flow in thin periodic domains is due to [1], followed by [2]. We refer to [18] for Bingham flows in periodic domains of infinite length.…”
Section: (): V-volmentioning
confidence: 98%
“…Theorem 4.3 (Darcy's law for VTPM). Consider δ ∈ (0, 1), γ ≤ 1 and C(δ) defined by (8). Then, there exists ṽ ∈ H 1 (0, 1; L 2 (ω) 3 ) with ṽ3 = 0 and ṽ = 0 on z 3 = {0, 1}, and P ∈ L C(1) 0…”
Section: Description Of the Tpmmentioning
confidence: 99%
“…Studies related to Newtonian fluids through TPM can be found in Anguiano and Suárez-Grau [11,14], Armiti-Juber [16], Bayada and et al [17], Larsson et al [26], Suárez-Grau [31], Valizadeh and Rudman [32], Wagner et al [33] and Zhengan and Hongxing [36]. Concerning generalized Newtonian fluids see Anguiano and Suárez-Grau [7,12,15], for Bingham fluids see Anguiano and Bunoiu [8,9], for compressible and piezo-viscous flow see Pérez-Ràfols et al [27], and for micropolar fluids see Suárez-Grau [30] and for diffusion problems see Anguiano [5,6] and Bunoiu and Timofte [21].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the generalized Newtonian fluids obeying the power law in the thin porous media Ω ε have been studied rigorously in Anguiano and Suárez-Grau [10] where we have obtained a 2D Darcy's law when the domain thickness tends to zero (see also [15] for the extension to the case of a thin porous media with an array of cylinders with small diameter). Also, the Bingham plastic behavior in the thin porous media Ω ε has been studied in [8,9]. For other studies concerning thin porous media, we refer to Anguiano [3,4,5,6,7], Anguiano and Suárez-Grau [11,12,14], Jouybari and T. S. Lundström [29], Prat and Agaësse [33], Suárez-Grau [35], Yeghiazarian et al [36] and Zhengan and Hongxing [37].…”
Section: Introductionmentioning
confidence: 99%